2002
DOI: 10.1002/jbm.a.10376
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human bone‐derived cells grown on GRGDSP‐peptide bound titanium surfaces

Abstract: Various surface modifications have been applied to titanium alloy (Ti-6Al-4V) implants, in an attempt to enhance osseointegration; crucial for ideal prosthetic fixation. Despite the numerous studies demonstrating that peptide-modified surfaces influence in vitro cellular behavior, there is relatively little data reporting their effects on bone remodeling. The objective of this article was to examine the effects of chemically modifying Ti-6Al-4V surfaces with a common RGD sequence, a 15-residue peptide containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 45 publications
(58 reference statements)
0
50
1
1
Order By: Relevance
“…Studies have shown that RGD and related peptides are able to enhance osteoblast adhesion and migration 11,12) . Zreiqat et al 8) reported that human bone-derived cells on GRGDSP peptide-bound Ti surfaces displayed significantly increased levels of OC gene expression when compared to uncoated Ti. Furthermore, Ferris et al 6) found that RGD-coated Ti implants stimulated new bone formation in vivo, such that there was a significant increase in bone volume around Ti implants in rat femur after implantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that RGD and related peptides are able to enhance osteoblast adhesion and migration 11,12) . Zreiqat et al 8) reported that human bone-derived cells on GRGDSP peptide-bound Ti surfaces displayed significantly increased levels of OC gene expression when compared to uncoated Ti. Furthermore, Ferris et al 6) found that RGD-coated Ti implants stimulated new bone formation in vivo, such that there was a significant increase in bone volume around Ti implants in rat femur after implantation.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the GRGDSP peptide derived from FN had the highest cell attachment activity among these peptides tested 7) . In a separate study, Zreiqat et al 8) reported that cells derived from human bone cultured on GRGDSP peptide-bound Ti surfaces displayed significantly increased level of osteocalcin (OC) gene expression when compared to uncoated Ti. By means of an in vivo animal study, significantly improved mechanical fixation and increased bone formation were achieved around Ti implants coated with RGD peptides and implanted into the femoral condyles of dogs 9) .…”
Section: Introductionmentioning
confidence: 99%
“…At present, several methods have developed implant surface modifications to improve implant treatment [15][16][17][18][19][20], including antimicrobial peptide [15,16], RGD peptide [17,18] and recombinant bone morphogenetic protein (BMP)-2 [19,20]. Taking advantage of the biocompatible characteristics of the titanium surface, we also have attempted surface modifications using biomimetic DLC coated technique [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, osteoblasts on RGDC surfaces showed osteocalcin (OC) mRNA expression at day 15, that is significantly earlier as compared with controls: osteoblasts on Ti and RDGCcoated surfaces began to show OC mRNA expression just at day 21, providing evidence of the enhanced functions of osteoblasts cultured on the RGDC-modified surfaces. Zreiqat et al (2003) presented a very interesting paper that not only discusses the effect of surface-tethered RGD peptides on bone cells adhesion and differentiation, but also on bone remodelling. Briefly, a thirteen amino-acid RGD peptide Gly-Arg-Gly-Asp-Ser-Pro-Tyr-Gly-GlyGly-Gly-Gly-Cys (GRGDSPYGGGGGC) was linked to Ti-6Al-4V (Ti grade 5) surfaces aminated by silane chemistry, through the thiol on the cysteine residue and a maleimide coupler.…”
Section: Morramentioning
confidence: 99%